Effect of hospital interior environment and decoration on healthcare providers-patient communication: a case study of Sultan Ahmad Shah Medical Center and Kuantan Medical Center - Mohd Zainudin, Maizura; Asif, Nayeem; Mohd Zainudin, Nurhaizan; Mohd. Shah, Aida Nur Sharini (International Organization Center of Academic Research, 2023)
Several attempts have been made to understand the relationship between space and society and how building design and layout affect people's communication patterns, work effectiveness, and agility. In contrast to many public hospitals in Malaysia, private hospitals, through their understanding of space and building layout, have willingly invested significant money in spatial configuration and interior design to improve their performance as healthcare providers. However, literature on space configuration and how space and layout design influence the communication between healthcare providers and patients are scarce to date. This paper aims to highlight how different interior settings of public hospitals affect the effective communication pattern between healthcare providers and patients. A questionnaire survey was conducted among staff and patients of the two selected hospitals. The study's outcome suggests the preferred interior environment and decoration that would influence the communication pattern, agility, and mood of staff and patients by comparing the two hospitals.